Optical Hash Function for High Speed and High Security Algorithm using Ring Resonator System - Pakom Juleang; S. Mitatha (My University, 2021)
This work presents a novel security technique using the optical hash function to create a message digest algorithm in the wavelength domain. The optical devices used for high speed and high security algorithm handling comprised a PANDA ring resonator connected with an add/drop filter system. The PANDA ring resonator was introduced to access the dynamic behavior of bright-bright soliton collision within the modified add/drop filter. Outputs of the dynamic states formed key suppression as a high security application for optical cryptography. The add/drop filter was an essential device in the proposed design for optical hash function processing. Simulation outputs proved that the proposed technique obtained optical hash function in the wavelength domain for real time message digest creation. The wavelength of the data must be within 40% of the center wavelength of the system input signal. The integrity of the data was maintained by this highly secure process.
Keywords: Photonic and Optical Devices; Advanced Photonic Communication Systems; Neural Networks and Reservoir Computing